Pengujian Daun Pandan, Daun Salam, dan Batang Serai terhadap Mortalitas Kumbang Beras Sitophilus oryzae - Eko Apriliyanto; Sarno Sarno (Jurnal Teknologi Pangan dan Ilmu Pertanian, 2026)
The quality of rice that is suitable for consumption, one of which is determined by the absence of associated components when the rice is in storage. Rice storage is carried out by means of long shelf life and good rice quality. Damage to rice due to pest attacks causes a decrease in quality and quantity. Environmentally friendly efforts are needed to control the rice weevil Sitophilus oryzae using vegetable materials. This study sought to ascertain the death rate of rice weevils treated with lemongrass stem (Cymbopogon citratus), bay leaves (Syzygium polyanthum), and pandan leaves (Pandanus amaryllifolius). The study employed a fully randomized design with three treatments in the form of simplicia plant components. There were 21 study units because each treatment included seven repetitions. Each treatment used 20 rice weevil imago breeding results which were infested in a jar containing 200 g of rice for 4 weeks in the laboratory. The use of pandan leaf, bay leaf, and lemongrass simplicia at 7 days after treatment showed the proportion of rice weevil mortality was 59,29%, 39,29%, and 50,00%, respectively. As for the observations of 14 day after treatments, 21 day after treatments, and 28 day after treatments showed that the mortality rate of all rice beetles was above 50%. Regarding the percentage of rice powder, hollow rice, and rice weight loss, the findings of observations on rice weevil mortality did not reveal any significant variations across all treatments.